2009
DOI: 10.1097/prs.0b013e3181bcee87
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Healing of Surgical Incisions Created by the PEAK PlasmaBlade, Conventional Electrosurgery, and a Scalpel

Abstract: The PlasmaBlade is a promising new surgical instrument that provides atraumatic, scalpel-like cutting precision and electrosurgical-like hemostasis, resulting in minimal bleeding, tissue injury, and scar formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
117
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 27 publications
7
117
2
Order By: Relevance
“…Although the source of this false signal is not yet fully understood, current evidence from preclinical experiments points toward long-lived, thermally induced chemiluminescence (25). Because the emission seems to be related to temperature, which can reach up to 250°C at the tip of the diathermy device, electrosurgical devices that operate at much lower temperatures are currently being tested (26). In addition to potentially facilitating margin assessment on intact WLE specimens, an advantage of low-temperature devices over monopolar diathermy is the reduced collateral tissue damage, which could also improve the accuracy of assessing tumor resection margins on histopathology (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although the source of this false signal is not yet fully understood, current evidence from preclinical experiments points toward long-lived, thermally induced chemiluminescence (25). Because the emission seems to be related to temperature, which can reach up to 250°C at the tip of the diathermy device, electrosurgical devices that operate at much lower temperatures are currently being tested (26). In addition to potentially facilitating margin assessment on intact WLE specimens, an advantage of low-temperature devices over monopolar diathermy is the reduced collateral tissue damage, which could also improve the accuracy of assessing tumor resection margins on histopathology (27).…”
Section: Discussionmentioning
confidence: 99%
“…PEAK PlasmaBlade has an average operating temperature of 40-170°C when used during surgery. The zone of thermal injury in PEAK PlasmaBlade incision (0.6 cm) was significantly smaller when compared to electrosurgical cut or coagulation incisions (4 cm) 6 . Thus, PEAK PlasmaBlade can be used nearby critical structures with lesser risk of vascular injury.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, coblation tonsillectomy had shown a drastic decrease in postoperative pain comparing with conventional technique 8,9 . As for PEAK PlasmaBlade versus conventional surgery, one study showed significant reduction in thermal injury and improved wound strength and histology with better visual assesment of scars 6 . It has been shown that PEAK PlasmaBlade reduces level of inflammation, thus leading to good epithelization resulting in improved healing and cosmesis [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of plasmakinetic depends on a plasma formation that creates an electrically conductive cloud, when radiofrequency energy contacts tissue. 9 An advantage of plasmakineti is cutting the tissues at much lower average temparature (as low as 50°C) than conventional electrocautery. 10 In the PKVP procedure, the current between the active and return electrode forms a plasma ball, which vaporizes the tissue on contact with a very high temperature and low thermal mass.…”
Section: Discussionmentioning
confidence: 99%